2017 IEEE/ACM International Conference on Computer-Aided Design (ICCAD) 2017
DOI: 10.1109/iccad.2017.8203758
|View full text |Cite
|
Sign up to set email alerts
|

Obfuscating the interconnects: Low-cost and resilient full-chip layout camouflaging

Abstract: Abstract-Layout camouflaging (LC) is a promising technique to protect chip design intellectual property (IP) from reverse engineers. Most prior art, however, cannot leverage the full potential of LC due to excessive overheads and/or their limited scope on an FEOL-centric and accordingly customized manufacturing process. If at all, most existing techniques can be reasonably applied only to selected parts of a chipwe argue that such "small-scale or custom camouflaging" will eventually be circumvented, irrespecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…We assessed all flavors when applied at large scales for various benchmarks by 1) their APD cost, while taking our scheme end-to-end and evaluating GDSII layouts, and 2) their resilience against SATbased attacks while running the seminal attack [15], [31]. The exploratory study is detailed in [1]; we summarize it next.…”
Section: Concept and Camouflaging Primitivementioning
confidence: 99%
See 3 more Smart Citations
“…We assessed all flavors when applied at large scales for various benchmarks by 1) their APD cost, while taking our scheme end-to-end and evaluating GDSII layouts, and 2) their resilience against SATbased attacks while running the seminal attack [15], [31]. The exploratory study is detailed in [1]; we summarize it next.…”
Section: Concept and Camouflaging Primitivementioning
confidence: 99%
“…In short, we select the flavor exemplified in Fig. 4 for the remainder of our study, as we found empirically that it offers the best security-cost trade-off [1].…”
Section: Concept and Camouflaging Primitivementioning
confidence: 99%
See 2 more Smart Citations
“…See also Sec. 4.1. distinguishable traits of standard cells, e.g., using look-alike gates [24] or secretly configured MUXes [25], (ii) selective doping implantation for threshold-voltage-based obfuscation [26], [27], or (iii) rendering the BEOL wires and/or vias resilient against RE [28]. It is important to note that most schemes require alterations to the FEOL process, which can be complex and costly.…”
Section: Layout Camouflagingmentioning
confidence: 99%